POST-Disaster reconstruction: viability and implication of a modular construction approach - Iffah Abu Talib (Penerbit Universiti Kebangsaan Malaysia, 2023)
In the event of a disaster, substantial deaths and property damage are caused by an unexpected event. Residential buildings and infrastructure destruction has killed many and displaced thousands. Post-disaster reconstruction involves important, challenging, and time-consuming recovery steps, including the provision of permanent housing for the affected community. Implementing modular construction approach is suggested to overcome the situation. Therefore, the research objectives are to identify viability of the modular construction approach during post-disaster reconstruction, and to determine implication of modular construction approach post-disaster reconstruction. A set of questionnaire survey were conducted to 45 active construction players. Data were then analysed using Partial Least Square - Structural Equation Modeling (PLS-SEM), using path model and measurement model analysis. Viability and implications on utilisation of modular construction approach during post-disasters had emerged to the strategies of implementation in construction projects. The findings suggested that by knowledge sharing; develop more aesthetic options; improve process management and reduce industry barriers could accelerate the benefits of modular construction approaches during post-disaster reconstruction.